Temporal and spatial characteristics of vegetation coverage and their influencing factors in the Sugan Lake wetland on the northern margin of the Qinghai–Tibet Plateau - Kang, Man-Ping; Zhao, Cheng-Zhang; Li, Xiao-Ya; Ma, Min; Zhao, Xia-Wei (Frontiers in Ecology and Evolution, 2023)
Fractional vegetation coverage (FVC) is an important indicator of salt marsh development or reversal in arid desert areas. Many studies have emphasized the differences in factors affecting vegetation coverage (FVC) in different temporal and spatial scales. However, few studies have reported on the temporal and spatial variation in vegetation coverage and its response to climate and the hydrological environment in inland salt marsh wetlands. Based on a community survey, meteorological data, hydrological data, and Landsat remote sensing image data from 1990 to 2020 were collected. The characteristics of the spatial and temporal distribution of vegetation coverage in Sugan Lake wetland over the past 30 years were analyzed using a binary pixel model and a quantitative analysis of the response of vegetation coverage to hydrological and meteorological factors was undertaken. Our results showed that the dimidiate pixel model had high simulation accuracy in retrieving vegetation coverage in inland salt marsh wetlands. The vegetation coverage of Sugan Lake wetland increased from 1990 to 2020, and its annual average was 19.34%. The spatial distribution of vegetation coverage was patchy and decreased from the center to the edge of the wetland. Within the same period, the vegetation coverage showed an increasing trend in the Quan-shui and He-hong areas and a decreasing trend in the Shan-hong areas. Vegetation coverage was mainly affected by precipitation, the lake area, surface runoff, and groundwater depth. Vegetation coverage was significantly and positively correlated with precipitation (R2=0.56, P<0.01), lake area (R2=0.50, P<0.01), air temperature (R2=0.46, P<0.01), and river density (R2=0.52, P<0.01) and negatively correlated with groundwater depth (R2=−0.57, P<0.01) and residential density (R2=−0.38, P<0.05). Implicit in these findings are complex mechanisms of vegetation change that help prevent vegetation degradation in fragile ecosystems.